2011
DOI: 10.1016/j.jmb.2011.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Transcription Inhibition by Phage T7 gp2 Protein

Abstract: E. coli T7 bacteriophage gp2 protein is a potent inhibitor of host RNA polymerase (RNAP). Gp2 inhibits formation of open promoter complex by binding to the β′ jaw, an RNAP domain that interacts with downstream promoter DNA. Here, we used an engineered promoter with an optimized sequence to obtain and characterize a specific promoter complex containing RNAP and gp2. In this complex, localized melting of promoter DNA is initiated but does not propagate to include the point of the transcription start. As a result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 26 publications
1
38
0
Order By: Relevance
“…Instead, we find that the primary difference between promoter OCs with very different lifetimes is in the range of the lengths of the abortive RNAs produced by the fraction of nonproductive ITC at the promoter. It is possible that late-acting E. coli regulatory factors analogous to bacteriophage T7gp2 (55,56) exist that interact selectively with the different downstream structures of OCs with different lifetimes (1,29) to regulate initiation, but none have been discovered. We therefore propose that the longer abortive RNAs produced by long-lived, stable promoter OCs play regulatory roles.…”
Section: Hybrid Length For Promoter Escape and Its Correlation With Ocmentioning
confidence: 99%
“…Instead, we find that the primary difference between promoter OCs with very different lifetimes is in the range of the lengths of the abortive RNAs produced by the fraction of nonproductive ITC at the promoter. It is possible that late-acting E. coli regulatory factors analogous to bacteriophage T7gp2 (55,56) exist that interact selectively with the different downstream structures of OCs with different lifetimes (1,29) to regulate initiation, but none have been discovered. We therefore propose that the longer abortive RNAs produced by long-lived, stable promoter OCs play regulatory roles.…”
Section: Hybrid Length For Promoter Escape and Its Correlation With Ocmentioning
confidence: 99%
“…For in vitro footprinting experiments, dsDNA promoter fragments were prepared from 100-nucleotide oligonucleotides corresponding to the À65/+35 promoter positions, as described (Mekler et al 2011). In each case, either the nontemplate or template strand oligonucleotide was labeled with [g-32 P]-ATP at its 59 end.…”
Section: Footprintingmentioning
confidence: 99%
“…3 In previous work, we studied the molecular and structural basis of the mechanism by which T7 Gp2 inhibits the bacterial RNAp and our analyses revealed that Gp2 uses a multipronged strategy to inactivate the bacterial RNAp. 4,5 Such studies have broad implications not only in elucidating novel paradigms of bacterial transcription regulation, but also for uncovering strategies for development of novel antibacterial compounds targeting bacterial RNAp.…”
mentioning
confidence: 99%